EDUKASI PENINGKATAN MUTU REMAJA DI DESA KEDONGDONG - Royani Royani (Swadaya: Indonesian Journal of Community Empowerment, 2021)
There are many reasons why a person may get married early, one of which is astrong desire to get married at a young age, or a condition that can be deliberately calledupon. Intention Early marriage is a tendency for adolescents or those who want to getmarried under the age of 20. Increased willingness to marry can be resolved throughpsychoeducation. This study uses a pre-experiment planning method with a one-groupdesign of some pre-test and post-test. This method is given to a group that does not havea comparison group. From this we can conclude that psychoeducation can be used toreduce the intent of early marriage.Drugs abuse is widespread in different parts of the world. In Indonesia, the levelof illegal drugs is increasing every year. It turns out that most illegal drug users areadolescents and adults. The role of young people as potential talent as successors to thiscountry can be interpreted as not being able to function optimally. This happens to somedrug users. Early management is better than the future, and the ideals of teens in thecountry are undermined by illegal drugs.Adolescence is the transition from childhood to adulthood. This time is veryimportant as it is an important factor for the future of the country. Adolescentreproductive health is a healthy condition that includes reproductive systems, functions,and processes. Adolescent reproductive health education is important to prevent genderbased violence and sexual deviation in adolescence. Lack of reproductive education cancause unwanted things such as free sex, sexual violence, and deviant behavior. Cognitiveprophylactic methods can be performed between peers, between peer groups, or usingfacilitators.The purpose of this study was to investigate the effect of psychoeducation earlymarriage in reducing early marriage intentions in adolescents, provide counseling toteenagers, provide an overview of drugs and motivation from drugs and providemotivation to adolescent teenagers to always think and behave positively , and alsoprovide adolescent reproductive health education which includes adolescent growth anddevelopment and adolescent reproductive health problems in Kedongdong village.Keywords: Intentions Early Marriage, Drugs, Reproduction Health, Teenagers